A 90-day subchronic gavage toxicity study in Fischer 344 rats with 3-methylfuran. (January 2018) - Gill, S.; Kavanagh, M.; Cherry, W.; Bourque, C.; Caldwell, D.; Wang, G.; Bondy, G.
Abstract: A 90-day gavage study was conducted with 0.0, 0.02, 0.075, 0.25, 1.0 and 4.0 mg/kg bw/day dose groups of 3-methylfuran to identify a no-observed adverse effect level for hepatotoxicity and to characterize non-neoplastic effects including changes in gross anatomy, histopathology, clinical biochemistry and hematology. There were significant changes in the serum clinical biochemistry markers related to liver injury where males were more affected than the females for most parameters analysed. The serum liver injury marker γ−glutamyltransferase, alanine and aspartate aminotransferases were significantly increased in males in the 4.0 mg/kg dose group. Alkaline phosphatase was increased in females and males. There were increases in both gross and histological lesions in the liver of both sexes in addition to statistical differences in female liver weights at the 4.0 mg/kg bw/day dose. Significant increases in spleen weights were found in both genders. This was accompanied by a dose–dependent atrophy of both B- and T-cell regions in which the males were more affected. There were no significant changes in male kidney weights but there was microscopically decreased protein in the proximal tubules and crowding of their nuclei in the 4.0 mg/kg bw/day dose group. There were also significant changes in the kidney serum biomarkers including various electrolytes, blood urea nitrogen, creatinine and uric acid. A small, but significant increase in female kidney weights was observed and which increase was accompanied by changes in electrolytes, kidney specific markers and a dose-dependent increase in mineralization. In both genders, amylase decreased whereas lipase increased but these were not accompanied by any histological changes in the pancreas. Histopathological changes in the liver were observed consistently in male and female rats in the 0.25 mg/kg dose group and higher. Hence, a lowest observed adverse effect level (LOAEL) of 0.25 mg/kg bw/d and a no observed adverse effect level (NOAEL) of 0.075 mg/kg bw/day are proposed for 3-methylfuran-induced hepatic lesions in this study. Benchmark dose modelling based on a BMR of 10% change in lesion incidence, generated BMDLs10 of 0.08 mg/kg bw/day in male rats and 0.05–0.17 mg/kg bw/day in female rats for increased incidence of liver lesions. Highlights: First study to with 3-methylfuran to identify a no-observed adverse effect level for hepatotoxicity and to characterize non-neoplastic effects including changes in gross anatomy, histopathology, clinical biochemistry and hematology. There were significant changes in the serum clinical biochemistry markers related to liver injury. There were increases in both gross and histological lesions in the liver of both sexes. There were changes in the spleen. This was accompanied by a dose–dependent atrophy of both B- and T-cell regions, greater in the males than females. Benchmark dose modelling based on a BMR of 10% change in lesion incidence, generated BMDLs10 of 0.08 mg/kg bw/day in male rats and 0.05–0.17 mg/kg bw/day in female rats for increased incidence of liver lesions.